2009
DOI: 10.1097/paf.0b013e3181c17b2e
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Intrauterine Fetal Death in Parvovirus B19 Fetal Infection

Abstract: Parvovirus B19 infection during pregnancy can be transmitted to the fetus through the placenta. The consequences for the health of the fetus are very variable and can be very serious. They include intrauterine fetal death (IUFD) and miscarriage, which can lead to medico-forensic questions. For the most part, cases of IUFD take place during the second trimester of gestation and present an anatomopathologic picture characteristic of fetal infection with hydrops, placental edema, serous effusion, and erythroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Moreover, approximately 60% to 70% of all adults are protected by neutralizing B19 antibodies stemming from past B19 infections. Silingardi and coworkers 31 recently reported five cases of unexpected intrauterine fetal deaths due to B19 infection (these cases were not caused by transfusions). This underscores the danger of B19 infection in at‐risk patients, especially during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, approximately 60% to 70% of all adults are protected by neutralizing B19 antibodies stemming from past B19 infections. Silingardi and coworkers 31 recently reported five cases of unexpected intrauterine fetal deaths due to B19 infection (these cases were not caused by transfusions). This underscores the danger of B19 infection in at‐risk patients, especially during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The P blood group antigen, which serves as a receptor for B19, has been detected in villous trophoblast cells of placental tissues in varying amounts during the course of pregnancy; in the first trimester of pregnancy, the level of the P antigen is very high. This high level of globoside receptor in placental cells during early pregnancy may act as a pathway for B19 to be transmitted from mother to foetus whereby the virus can subsequently infect erythroid progenitor cells for replication (Heegaard & Brown 2002, Silingardi et al 2009). …”
mentioning
confidence: 99%
“…Transplacental transmission of parvovirus B19 during pregnancy is one of the leading causes of nonimmune foetal hydrops, spontaneous abortion or intrauterine foetal death (Skjöldebrand-Sparre et al 2000); it has been reported that intrauterine foetal death and miscarriage occur more during the second trimester (Johansson et al 2008, Silingardi et al 2009). Although B19 was initially discovered in 1974 (and the discovery published in 1975), it was not associated with disease until 1981, when it was linked to aplastic crisis, fifth disease, spontaneous abortion and acute arthritis (Cossart et al 1975, Heegaard & Brown 2002.…”
mentioning
confidence: 99%
“…Cytomegalovirus, rubella, mumps, herpes, human immunodeficiency virus, and parvovirus are among the most important infecting humans (Thompson and Glasgow, 1980;Al-Katawee et al, 2005;Ornoy and Tenenbaum, 2006;Chan et al, 2007;Benoist et al, 2008;Davis and Fernando, 2008;Rawlinson et al, 2008;Riipinen et al, 2008;Webster, 2008;Mihci et al, 2009;Rasmussen et al, 2009;Silingardi et al, 2009). Ljungan virus (LV) has emerged in the literature as a putative cause of afflictions in animals and potentially in humans.…”
Section: Introductionmentioning
confidence: 98%